MANAJEMEN KELAS DALAM MENINGKATKAN BELAJAR SISWA SEKOLAH DASAR - Ninik Hidayati (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
The purpose of this study is to describe class management planning, implementation of class management, supervision of class management and supporting factors and inhibiting factors in class management in improving elementary school student learning. This research method is descriptive qualitative. The results showed that classroom management planning was carried out by arranging facilities, teaching management and student management, class management was carried out by applying some class management principles and several approaches, supervision was carried out continuously, supporting factors and inhibiting factors in class management were physical, social environment emotional state and organization.